Antocha crane flies from Taiwan (Diptera: Limoniidae: Limoniinae) - Podenas, Sigitas; Young, Chen W. (Zootaxa, 2015)
Taiwanese species of the crane fly subgenus Antocha (Antocha) Osten Sacken, 1860, are reviewed. Antocha (Antocha) taiwanensis, new species, is described and figured. Previously known species, Antocha (A.) bifida Alexander, 1924a and Antocha (A.) styx Alexander, 1930 are redescribed and illustrated. Antocha (A.) javanensis Alexander, 1915 is removed from the list of Taiwanese crane flies. Antocha (A.) gracillima Alexander, 1924b and species close to Antocha (A.) streptocera Alexander, 1949 are listed for the first time in Taiwan. Identification key for all Taiwanese Antocha species is given.